THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON TEACHERS’ PERFORMANCE AT SMPN 16 PONTIANAK - admin, INDRI WULANDARI B12111024 (Jurnal Manajemen Update, 2015)
Abstract This research entitled "The Influence of Motivation and Work Environment on Teachers’ Performance at SMPN 16 Pontianak". The problem in this research is how motivation, work environment and performance at SMPN 16 Pontianak and the influence of motivation and work environment partially on the performance of teachers at SMPN 16 Pontianak. In this research, motivation interpreted as an effort to encourage teacher to do the job, while work environment means everything that is around teachers or everything that surrounds a teacher's work that can affect them in performing the tasks assigned. Performance is defined as the record of outcomes produced or a specific job function or activity during a specific period. The purpose of this study was to determine the description of motivation, work environment and performance at SMPN 16 Pontianak and analyze how much the influence of motivation and work environment on teachers’ performance at SMPN 16 Pontianak partially. The method used in this research is questionnaire as data collection techniques. The sample in this study was saturated sampling means that all teachers of SMPN 16 Pontianak sampled. This study measured using a Likert scale and analyzed using SPSS 18 for test of validity, reliability, classic assumption test, R square test and T test in order to analyze the relationship of all variables. Based on the research results, it can be known that motivation gives significant effect while work environment does not give significant effect on teachers’ performance at SMPN 16 Pontianak. Keywords: Motivation, Work Environment, Teacher Performance